Do Digital Competencies Matter? : Exploring Entrepreneurial Education, Self-Efficacy, and Intention Among Gen Z in Indonesia - Kenang, Irantha Hendrika; Puspita, Shandy; Wijayadne, Devi Rahnjen (Bina Nusantara University, 2025)
This research aimed to thoroughly examine the influence of digital competencies on the relationship between entrepreneurial education, entrepreneurial self-efficacy, and entrepreneurial intention among Generation Z (Gen Z) university students in Indonesia. Considering that digital technologies increasingly shape entrepreneurial landscapes, understanding the extent to how digital competencies contribute to entrepreneurial development is very important, specifically among youth who are often described as digital natives. To achieve the stated objective, a quantitative survey design was adopted, involving 190 undergraduate students who had completed entrepreneurship education programs across several Indonesian universities. Accordingly, data collection was conducted from February to April 2025 using online questionnaires. The obtained responses were subsequently analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the direct, mediating, and moderating relationships among the variables. The results show that entrepreneurial education significantly enhanced entrepreneurial intention both directly and indirectly through entrepreneurial self-efficacy. Within this context, self-efficacy played a mediating role by translating the impact of education into intention, thereby emphasizing the importance of confidence-building as a mechanism for fostering entrepreneurial motivation. However, digital competencies do not significantly moderate the relationship between education and intention, nor between self-efficacy and intention. This suggests that while Gen Z students may be digitally fluent in everyday contexts, digital competencies alone are not sufficient to amplify entrepreneurial outcomes. The observations made invariably implied that although confidence and practical, hands-on entrepreneurial education are essential for fostering entrepreneurial intention in Gen Z, general digital literacy alone may not suffice.